APPLICATION OF TECHNOLOGY AUGMENTED REALITY IN BROCHURES SMK GHAMA CARAKA DEPOK BASED ANDROID - Indarti Indarti; Dewi Laraswati (Kresnamedia Publisher, 2020)
The brochure is one of the important instruments for promotion to provide initial information for prospective students, but the currently used brochure is still fairly classic. Still using brochure leaflets on paper media and the information conveyed depends on the size of the printed brochure. If the school committee wants to provide more information by adding pictures with product details, the larger the brochure size that needs to be printed. The research used augmented reality to make interactive brochures based on Android. The steps involved are analyzing the software and hardware requirements to be used. The research method uses the case study method with a qualitative approach. As for the application development model using the waterfall model, which is a method in SDLC, the sequence of steps used in this research is system requirement analysis, design, program code making, testing, and support.